1989
DOI: 10.1099/0022-1317-70-5-1053
|View full text |Cite
|
Sign up to set email alerts
|

Organization and Interviral Homologies of the 3'-terminal Portion of Potato Virus S RNA

Abstract: SUMMARYThe sequence of 3553 nucleotides corresponding to the 3'-terminal region of potato virus S (PVS) has been determined from cloned cDNA. The sequence obtained contains six open reading frames (ORFs) encoding proteins of Mr 10 734, Mr 32 515, Mr 7222, Mr 11 802, Mr 25092 and at least Mr 41052. The sequence of the 33K ORF has been confirmed to be that of the viral coat protein gene. The nucleotide sequence of this ORF was obtained from plasmids which were isolated by colony hybridization with a specific mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
45
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 20 publications
4
45
0
1
Order By: Relevance
“…The viral genome consists of one single-stranded, positive sense RNA molecule with an estimated Mr of 2.4 × 106 which contains a T-terminal polyadenylated region. Recent nucleotide sequence data from PVS (MacKenzie et al, 1989) and a related carlavirus, potato virus M (PVM) (Rupasov et al, 1989), have demonstrated that these two viruses have genome organizations similar to that of potato virus X (PVX) (Huisman et al, 1988) and other members of the potexvirus group. The viral genome of PVS contains six open reading frames (ORFs) which encode polypeptides with Mr of 10734, 32515, 7222, 11802, 25092 and more than 41052.…”
Section: Potato Virus S (Pvs) Is a Member Of The Carlavirus Groupmentioning
confidence: 99%
See 3 more Smart Citations
“…The viral genome consists of one single-stranded, positive sense RNA molecule with an estimated Mr of 2.4 × 106 which contains a T-terminal polyadenylated region. Recent nucleotide sequence data from PVS (MacKenzie et al, 1989) and a related carlavirus, potato virus M (PVM) (Rupasov et al, 1989), have demonstrated that these two viruses have genome organizations similar to that of potato virus X (PVX) (Huisman et al, 1988) and other members of the potexvirus group. The viral genome of PVS contains six open reading frames (ORFs) which encode polypeptides with Mr of 10734, 32515, 7222, 11802, 25092 and more than 41052.…”
Section: Potato Virus S (Pvs) Is a Member Of The Carlavirus Groupmentioning
confidence: 99%
“…Samples of leaf tissue (100 mg) were homogenized with 100 ~tl of SDS-PAGE sample buffer (4~ SDS, 125 mMTris-HCl pH 6-8, 10~ 2-mercaptoethanol, 0.04~ bromophenol blue, 20~ glycerol) and incubated at 95 °C for 5 min. Following centrifugation at 13000 r.p.m, for 5 rain in an Eppendorf microcentrifuge, 15 ~tl aliquots were loaded onto a 12~ polyacrylamide gel and, after electrophoresis using the buffer system of Laemmli (1970), separated proteins were blotted onto Immobilon membranes (Millipore) and probed with 1G 11 MAb and l zSI-labelled goat anti-mouse Ig as previously described (MacKenzie et al, 1989). Approximately 40~ of the transgenic plants obtained expressed detectable levels of PVS coat protein as judged by immunoblotting.…”
Section: Potato Virus S (Pvs) Is a Member Of The Carlavirus Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…Pairwise computer alignments between available nucleotide sé-quences of PVY (Robagliaef a/. 1989) and PVS (McKenzie et al 1989) revealed a 72% homology for a région of 93 residues located at 2500 (PVY) and 2800 (PVS) residues downstream their 3' end (data not shown). Homology even reached 81% for a stretch of 26 nucleotides.…”
mentioning
confidence: 98%